FUNGSI KOORDINASI DINAS LINGKUNGAN HIDUP DAN KEHUTANAN PROVINSI KEPULAUAN RIAU DAN DINAS LINGKUNGAN HIDUP KOTA TANJUNGPINANG DALAM PENGAWASAN HUTAN MANGROVE DI KOTA TANJUNGPINANG - Shahril Budiman; Ilham Riady Prayoga; Zamzami A Karim; Junriana Junriana (Governance, 2023)
The purpose of the study was to determine the Coordination Function of the Environment and Forestry Service of the Riau Islands Province and the Tajungpinang City Environmental Service in Monitoring Mangrove Forests in Tanjungpinang City. In this study, the theory used by Hasibuan (2019:88). The population in the study amounted to 8 people, the data analysis used in this study was a qualitative descriptive data analysis technique. The conclusion obtained is that the Coordination Function of the Environment and Forestry Office of the Riau Islands Province in Supervision of Mangrove Forests in Tanjungpinang City is in accordance with their respective authorities although several things need to be improved. Then for the socialization that was carried out both to the community and to employees, it was found that the socialization was not comprehensive. Because the socialization carried out only in general terms, such as raising the theme of cleanliness and environmental protection, has not focused on monitoring mangroves. Before being able to implement a policy, the implementor must realize that a decision has been issued, there are often misunderstandings about the decisions that have been issued so that there are no misunderstandings, socialization must be carried out and that everything is coordinated even though it only occurs when the RTRW is drafted and problems are related to mangroves